PENINGKATAN LITERASI KEUANGAN BAGI ANGGOTA KOPERASI PEMBERDAYAAN UMMAT DAARUT TAUHID UNTUK PENGELOLAAN KEUANGAN YANG BERKELANJUTAN - Riski Dwi Nugroho; Dede Hendra; Muhamad Nurhamdi (Abdi Jurnal Publikasi, 2025)
Low levels of financial literacy remain a challenge in personal financial management, including among cooperative members. The Student Creativity Program (PKM) aims to improve the financial literacy of members of the Daarut Tauhid Community Empowerment Cooperative through an educational approach based on Islamic values. The program involved training, simulations, and group discussions involving 40 active participants. Pre- and post-test results showed a significant increase in participants' understanding of financial planning, debt management, and the importance of financial record-keeping. An educational module was also developed as a practical guide for participants. This activity encouraged the formation of financial study groups as a form of program sustainability. In conclusion, community-based financial literacy education and spiritual values are effective in encouraging changes in wiser and more sustainable financial behavior.